The potential of DBP gels containing intervertebral disc cells for annulus fibrosus supplementation:in vivo. (4th March 2013) - Song, Jeong Eun; Kim, Eun Young; Ahn, Woo Young; Lee, Yu Jeong; Lee, Dongwon; Reis, Rui; Khang, Gilson
Abstract: Demineralized bone particle (DBP), which is widely used as a biomaterial in the field of tissue engineering, contains various bioactive molecules, such as cytokines. For this reason, in this study we investigated the effects of injectable DBP gels on cell proliferation, inflammation and maintenance of the shape of DBP gels as a scaffold able to substitute for intervertebral discs (IVDs) in vivo . DBP gels were fabricated with different percentages (5% and 10%) of DBP powder and 3% acetic acid, including 0.02% pepsin. DBP gels with 1 × 10 6 annulus fibrosus (AF) cells were implanted into the dorsal subcutaneous region of BALB/C‐nu mice for 1, 2 and 3 weeks. Cell proliferation was measured by MTT assay. The effect of DBP gels on the inflammatory response was analysed by measuring the amount of tumour necrosis factor‐alpha (TNF α ) released. Also, histological methods were carried out to analyse the response of DBP gels in vivo . This study demonstrated that injectable DBP gels are able to provide physical scaffolds for growing IVD cells in vivo . Copyright © 2013 John Wiley & Sons, Ltd.